Factors Affecting Male Consumer Online Buying Behaviour - Kausar Jiwa; Amran Harun; Yuary Farradia; Noreina Nasir; Nur Aniza Quantaniah Jusoh (CV ODIS, 2022)
Online shopping today has become a way of life for people worldwide as they spend so much at the workplace rather than at home with family. Importantly, even though males have been more willing to engage in e-commerce than females, there is still a lack of information and studies emphasizing male online behavior. Thus, this study aims to identify how time-saving and technology influence purchasing behavior among male online consumers. In addition, this study used a quantitative method by using an online survey of 384 male online shoppers at four different platforms: Facebook, Instagram, WhatsApp, and Shopee. Each platform used quota sampling, snowball sampling, and convenience sampling methods. Statistical Packages for Social Science (SPSS) software was used to analyze data from the survey. The multiple regression analysis indicated that one factor has a significant relationship with male online purchase behavior: time-saving. This finding is essential for marketers to ease the use of online shopping platforms to save more time and encourage more males to purchase online. This study is also essential for the researcher to deeply understand the factors affecting male consumers' online buying behavior